Falls and delirium in an acute care setting: A retrospective chart review before and after an organisation‐wide interprofessional education. Issue 7 (13th March 2018) - Babine, Rhonda L; Hyrkäs, Kristiina E; Hallen, Sarah; Wierman, Heidi R; Bachand, Deborah A; Chapman, Joanne L; Fuller, Valerie J
Abstract : Aim and objectives: To describe and compare identification of delirium, length of stay and discharge locations in two patient samples of falls, before and after an organisation‐wide interprofessional delirium education and practice change along with implementation of a policy. Background: Delirium is a common and severe problem for hospitalised patients, with occurrence ranging from 14%–56%, morbidity and mortality from 25%–33%. Recent studies report that 73%–96% of patients who fell during a hospital stay had symptoms of delirium; however, the delirium went undiagnosed and untreated in 75% of the cases. Design: A descriptive, retrospective observational study using a pre/postdesign. Methods: Two chart reviews were performed on patient falls as identified in the hospital safety reporting system in 2009–2010 (98 fallers) and 2012 (108 fallers). An organisation‐wide education was planned and implemented with monitoring of policy compliance. Results: After the education, documentation of the "diagnosis of delirium" and "no evidence of delirium" increased from 14.3%–29.5% and from 27.6%–44.4%. The documentation of "evidence of delirium" decreased significantly from 58.2%–25.9% ( p < .001). The confusion assessment method (CAM) identified the diagnosis of delirium at 76% accuracy. The length of stay decreased by 7.3 days. The fall rates in 2011 and 2012 were 3.01 and 2.82 falls per 1, 000 patient days and in 2013 decreased to 2.16. Conclusion: The results indicate that improving delirium recognition and treatment through interprofessional education can reduce falls and length of stay. Relevance to clinical practice: The results demonstrate that when staff learn to prevent, identify, manage and document delirium more accurately the fall rate decreases. The practice change, including the use of CAM, was sustained by continuous auditing including re‐education, and the re‐enforcement of learning along with the implementation of a policy.